Novelistic Inquiry for Answerability in Organization Development - Ahmad, Che Mahzan (IDOSI Publication, 2010)
The purpose of this conceptual article is to expand and extend Bakhtin’s theory of novel and to explore their relevance to organization development practice and research, in particular that relates to the ‘sacred’ type of inquiry. We placed organization development inquiry as a ‘signed’ act within Bakhtin’s moral philosophy whereby it is interpreted in the context of real-life authorship experience. The architectonic of the novel rejects the monologism over the ‘second’, the ‘living knower’. The ‘second’ is the addressee with equal rights to be heard and to be answered. In this enterprise for blossoming participation, both the ‘first’ and the ‘second’ are accountable to the Third (super-addressee). Albeit of centripetal-centrifugal struggle for supremacy of consciousness, penetration/inter-penetration with others ideas is fundamental activity of genuine novelistic living life. Answerability meanwhile is central to the above architectonics where responsibility functions as a non-alibi in being. Novelistic inquiry highlighted the aesthetic nature of subject-subject relationships in dialogic encounters, which in so doing offer an inherent challenge to traditional forms of inquiry in organization development. The article offers insights and wisdom excavated from the literary theory for organization development.